Penerapan Model Pembelajaran Inkuiri Berbasis Google Classroom untuk Meningkatkan Kemampuan Berfikir Kritis dan Aktivitas Belajar PAI dan Budi Pekerti pada Peserta Didik SMA Negeri 1 Selong - Asmuni Asmuni (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
This study aims to apply a google classroom-based inquiry learning model to improve critical thinking skills and learning activities of Islamic Education and Characteristics of munakahat material in class XII MIPA-4 SMAN 1 Selong students in the 2020/2021 school year. This research method is a classroom action research which takes place in two cycles which are carried out online. The subjects of this study were 35 students of class XII MIPA-4. Data collection techniques were carried out by tests and observations. The collected data were analyzed descriptively qualitatively. The results obtained were (1) the increase in critical thinking skills of students as evidenced by the learning outcomes of the original knowledge aspects at an average of 72, increased to 83 in the first cycle, and increased again to 85 in the second cycle, while the learning outcomes of the aspects of learning. Initial skills at initial conditions averaged 69, increased to 78 in cycle I, and increased again to 86 in cycle II. For the percentage of learning completeness (knowledge), students who completed from the initial conditions were 22.86% (8 people), increased by 62.86% (22 people) in cycle I, and increased again 91.43% (32 people) in the cycle II. Completeness of learning (skills), students who completed from the initial conditions 22.86% (8 people), increased 62.86% (22 people) in cycle I, and increased again 91.43% (32 people) in cycle II; and (2) increased learning activities of students as evidenced by an increase in learning activities, namely 71.43% (active category) in cycle I, increasing to 94.29% (very active category) in cycle II.